The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1039/b407801b
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of homolytic and heterolytic pathways in the photodissociation of iminosulfonates and direct detection of the p-toluenesulfonyloxyl radical

Abstract: The mechanistic aspects of the photochemistry of several iminosulfonate photoacid generators (PAGs) have been studied based on product analysis, nanosecond laser flash photolysis, and determination of acid generation efficiencies. Our findings support a competition between homolytic and heterolytic N-O dissociation mechanisms. By measuring the efficiencies of acid generation for each PAG in the presence and absence of an ion quencher, we were able to roughly quantify the degree of branching between heterolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
(7 reference statements)
1
11
0
1
Order By: Relevance
“…A transient structureless absorption band at λ max ≈450 nm with a lifetime of 7–20 μs was assigned to this radical, and its photoinduced ( λ max =480 nm) dissociation into CH 3 and SO 3 was proposed 7. A similar transient absorption band was also observed for the putative p ‐toluenesulfonyloxyl radical ( λ max =540 nm) in CH 3 CN solution during laser ( λ =266 nm) photolysis of iminosulfonates 8. The formation of CH 3 SO 3 was reported by electron beam irradiation (3 MeV) of the CH 3 SO 3 − ion in ionic liquids at 77 K,9 and very recently by the reaction of methylsulfinyl radicals (CH 3 SO) and molecular oxygen ( 3 O 2 ) in solid argon 10…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…A transient structureless absorption band at λ max ≈450 nm with a lifetime of 7–20 μs was assigned to this radical, and its photoinduced ( λ max =480 nm) dissociation into CH 3 and SO 3 was proposed 7. A similar transient absorption band was also observed for the putative p ‐toluenesulfonyloxyl radical ( λ max =540 nm) in CH 3 CN solution during laser ( λ =266 nm) photolysis of iminosulfonates 8. The formation of CH 3 SO 3 was reported by electron beam irradiation (3 MeV) of the CH 3 SO 3 − ion in ionic liquids at 77 K,9 and very recently by the reaction of methylsulfinyl radicals (CH 3 SO) and molecular oxygen ( 3 O 2 ) in solid argon 10…”
mentioning
confidence: 65%
“…[7] As imilar transient absorption band was also observed for the putative p-toluenesulfonyloxyl radical (l max = 540 nm) in CH 3 CN solution during laser (l = 266 nm) photolysis of iminosulfonates. [8] Thef ormation of CH 3 SO 3 was reported by electron beam irradiation (3 MeV) of the CH 3 SO 3 À ion in ionic liquids at 77 K, [9] and very recently by the reaction of methylsulfinyl radicals (CH 3 SO) and molecular oxygen ( 3 O 2 )i ns olid argon. [10] Themolecular structures and the thermodynamic properties of CH 3 SO 3 and various isomers have been calculated at different theoretical levels.…”
mentioning
confidence: 99%
“…They constitute an important class of cationic photoinitiators which have a strategic position in the polymer industries 14,15 . Commercially available PAGs are mainly photoactivated through direct excitation at wavelengths ranging from VUV to close UV [16][17][18][19][20][21][22] . Moreover they exhibit very low 2PA crosssections because of their limited -conjugation 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the mechanistic studies as reported by Scaiano and his coworkers 27 and Shirai et al 28 for the photolysis of oxime sulfonates and from our solvent investigation, we proposed the possible mechanism for the photogeneration of acids. On excitation, both the carboxylates and sulfonates of 1-acetylferroceneoxime (3a-d and 4a-d) undergo homolytic N-O bond cleavage from the singlet excited state to generate an iminyl and acyloxy or sulfonyl radical pair (Scheme 3).…”
Section: Mechanism For the Photogeneration Of Carboxylic And Sulfonic...mentioning
confidence: 55%